Approbation of the method for determination of PAI-1 - Nalbat, Alena; Kharchenko, Svitlana; Yatsenko, Tetiana (Problems of Environmental Biotechnology, 2021)
A method for determining the activity of РAI-1 is proposed, which allows determining the level of this inhibitor quickly and with high accuracy and can be used as a tool for diagnosing the development of cardiovascular diseases.